An experimental study on the effects of needle dynamics on the penetration of a high-pressure methane jet. (1st October 2019) - Vera-Tudela, W.; Kyrtatos, P.; Schneider, B.; Boulouchos, K.; Willmann, M.
Highlights: High pressure gas injection using a prototype fuel injector. Needle movement measurements and schlieren optical technique. Needle profiles presented strong dependency on injection pressure. Tip penetration and needle movement showed negligible differences at high injection pressures. Abstract: The aim of this work was to investigate the needle dynamics of a prototype gas injector under different working conditions. Furthermore, the consequences that these effects would have on the propagation of a high-pressure gas jet in a quiescent environment. To achieve this, two experimental matrices were designed: The first one included variations of the injection pressure, control pressure and injection duration, this was done in order to analyze the movement of the needle. On the second one, the injection and chamber pressure, and consequently the pressure ratio, were changed for the study of the jet penetration. The experiments were carried out in a constant volume cell equipped with optical accesses, This allowed the application of the schlieren technique and therefore the quantification of the propagation of the jet through the ambient gases was possible. The injector used was a single-hole axial injector working with methane as the injection fluid and diesel as the control fluid; different sensors built into the nozzle allowed the needle movement to be recorded as a function of time. The results showed a strong dependency of the needle dynamics on the injection pressure and the control pressure. However, this dependency is less noticeable at higher injection pressures, and in some cases even negligible. The chamber pressure proved to have a small but still noticeable effect on the needle dynamics. For the cases where the conditions seem to have no effect on the needle dynamics, the penetration results showed tendencies which coincided with the theory and literature.